A Dialectical Analysis Of Fiqh And Scientific Perspectives On Qibla Direction Of Ancient Mosques In Lombok - Muhammad Awaludin; Ahamd Izzuddin; Agus Nurhadi (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Qibla direction is a valid requirement in performing prayer. But then the understanding of Qibla direction becomes divided into two, the perspective of science and fiqh. These two opinions are then dialectic on ancient mosques in Lombok, where the Qibla direction is only based on the guidance/jihad of the wali/ulama. Methodology used in this research is qualitative research with the type of field research and socio-historical approach. The results of this study showed that the dialectic of Qibla direction on ancient mosques in Lombok can still be maintained and is still considered valid. This argument uses the fiqh argument that the Qibla direction is jihadul ka'bah. But certainly the fiqh perspective of jihadul ka'bah is no longer relevant if it is associated with measuring the Qibla direction in the construction of modern mosques.